Implementasi Profil Pelajar Pancasila Untuk Memperkuat Karakter Siswa Kelas X SMA Negeri 1 Palangka Raya - Anggun Anggraini; Eddy Lion; Eli Karliani (FKIP, Universitas Palangka Raya, 2023)
This research aims to describe and analyze the form of implementation, supporting factors, inhibiting factors, and solutions in implementing the Pancasila student profile to strengthen the character of class X SMA Negeri 1 Palangka Raya students. This research uses qualitative methods with the type of research being descriptive. The research subjects consisted of the Principal of SMA Negeri 1 Palangka Raya City, Deputy Principal of SMA Negeri 1 Palangka Raya for curriculum, Deputy Principal of SMA Negeri 1 Palangka Raya for Student Affairs, Civics Teachers, Teachers of other subjects, and 5 Students. Data collection uses observation, interviews and documentation methods. Meanwhile, the data analysis technique steps in this research are data collection, data reduction, data presentation, and drawing conclusions. The results of this research are (1) a form of implementation of the Pancasila Student Profile to strengthen the character of class Spiritual tourism and so on which are strengthened by the implementation of the Pancasila Student Profile Strengthening Project (P5), (2) The supporting factors are cooperation between school members, good student character, coordination between teachers, facilities and infrastructure as well as well-designed activities. Meanwhile, the inhibiting factor is the teacher's schedule which collides with the teaching schedule in classes XI-XII which still uses the K-13 curriculum. Then students feel a little burdened with assignments that are quite expensive and assignment deadlines that are too fast. (3) The solution to overcome this obstacle is that all school members have the right to give their opinions and students manage their time and set aside pocket money to save